x86-64 Assembly Language Programming with Ubuntu - Jorgensen, Ed (Open textbook library., 2019)
The purpose of this text is to provide a reference for University level assembly language and systems programming courses. Specifically, this text addresses the x86-64 instruction set for the popular x86-64 class of processors using the Ubuntu 64-bit Operating System (OS). While the provided code and various examples should work under any Linux-based 64-bit OS, they have only been tested under Ubuntu 14.04 LTS (64-bit). The x86-64 is a Complex Instruction Set Computing (CISC) CPU design. This refers to the internal processor design philosophy. CISC processors typically include a wide variety of instructions (sometimes overlapping), varying instructions sizes, and a wide range of addressing modes. The term was retroactively coined in contrast to Reduced Instruction Set Computer (RISC3).